Field Studies on Lyme Disease in North America - Joseph Piesman (Canadian Journal of Infectious Diseases)
The primary tick vector of Borrelia burgdorferi in eastern and central North America is Ixodes dammini; in western North America, Ixodes pacificus. Searching for the appropriate vector is the first step in determining whether a region is endemic and enzootic for the spirochete B burgdorferi, the etiological agent of Lyme disease, followed by examination of the ticks (questing or already attached to hosts) and wildlife for the spirochete. Questing ticks can be collected through a variety of methods. The two major animal hosts for I dammini are the white-footed mouse Peromyscus leucopus and the white-tailed deer Odocoileus virginianus. Sampling strategies should consider habitat and season. All three life stages of the vector tick should be located, indicating a self-sustaining population. Although B burgdorferi can be detected in many ways, there is no substitute for isolating the spirochete in Barbour-Stoenner-Kelly II medium for definitive proof of the presence of the Lyme disease spirochete.